Efficient traceable identity-based signature scheme - DU Hong-zhen1; WEN Qiao-yan2 (Tongxin xuebao)
The inherent key escrow problem is a main disadvantage in identity-based signature schemes. The concept and security model of traceable identity-based signature （T-IBS） was introduced which was a new approach to mitigate the key escrow problem in identity-based signature schemes. Moreover, a T-IBS scheme without pairing was presented and the security of the provided scheme was provided under the elliptic curve discrete logarithm assumption and the random oracle model. Compared with the existing schemes without suffering from key escrow, the scheme is the most efficient scheme and the signing algorithm needs only one scalar multiplication in the additive group while the reverse operation requires only three scalar multiplications.